WEED CONTROL AND PERFORMANCE OF JUVENILE SWEET ORANGE TREES UNDER HERBICIDE ROTATIONS - Olawale O. Alamu; Rafiat K. Egberongbe; Tajudeen B. Akinrinola (Agricultura)
Weeds interfere reduce the growth and yield of citrus trees. The use of herbicides to reduce labour demand in suppressing weeds is challenged by weed tolerance to the repeated application of herbicides with the same mode of action. However, an adequate understanding of herbicide rotation on weeds and citrus tree performance is limited. This study aimed to investigate juvenile sweet orange trees as affected by herbicide repetition. Repeated application of paraquat dichloride 276 a.i/L at 4 L/ha, glyphosate 480 a.i/L at 6 L/ha, paraquat followed by (fb) glyphosate, glyphosate fb paraquat, hand slashing (HS) and control variant (without treatment) were evaluated in a randomised complete block design with four replicates. Sweet orange seedlings were spaced at 5 × 5 m2 on a 50 × 20 m2 field/treatment. Data on Weed Control Efficiency (WCE), weed biomass (g/m2), citrus height (m) and fruits yield (kg/plant) were analysed using descriptive statistics and ANOVA at P<0.05. The results revealed that the WCE of glyphosate fb paraquat (95.2%) and glyphosate (93.3%) were similar but differed significantly from the other treatments. The weed dry biomass was in the order: 62.7 (glyphosate fb paraquat)< 71.9 (glyphosate)< 118.3 (paraquat)< 134 (paraquat fb glyphosate)< 181.7 (HS)< 441.7 (control). Citrus heights ranged from 2.7 (control) to 4.3 (glyphosate). Sweet orange fruit yield was in the order: 69.5 (glyphosate) >66.0 (HS) >65.3 (paraquat) >62.5 (glyphosate fb paraquat) >52.0 (paraquat fb glyphosate) >46.0 (control). Rotating glyphosate followed by paraquat dichloride was suggested for suppressing weeds and improving sweet orange fruit yield.